UJI DAYA HASIL UBIKAYU (Manihot esculenta Crantz) VARIETAS UJ5 PADA BERBAGAI UMUR PANEN - Puspitorini, Palupi; Pitaloka, Dyah; Kurniastuti, Tri (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2016)
This study aims to find out the results of cassava tuber crop UJ5 variety at different harvest ages. Research direction is that cassava varieties have been planted throughout Indonesia as the best producer of cassava varieties. High levels of starch and high HCN content makes this variety was selected by the factory - tapioca factory in Indonesia. Research design used randomized block design with 7 treatments of harvesting (UP) were repeated 3 times. UP6 (harvesting 6 MAP), UP7 (harvesting 7 MAP), UP8 (harvesting 8 MAP), UP9 (harvesting 9 MAP), UP10 (harvesting 10 MAP), UP11 (harvesting 11 MAP), UP12 ( harvesting 12 MAP). The research variables are the fresh weight of tuber, tuber starch content (%), the weight of biomass, harvest index, number of tubers per plant. The results showed that the best harvesting time is UP9 the results did not differ with UP10, UP11 and UP12